The emergence of chromosomally located blaCTX-M subtypes in Salmonella enterica serotype Kentucky ST198 isolated from diarrhea patients, food, and environmental sources in Henan, China - Qi, Haoyu; Li, Menghan; Li, Yanfen; Li, Ruichao; Cui, Ying; Wu, Lingling; Zhang, Meng; Zhang, Guangwei; Li, Yongli (Frontiers in Microbiology, 2026)
IntroductionRecently, with the resistance to medically important antimicrobial agents, Salmonella enterica serovar Kentucky ST198 has attracted continuous attention. In this study, we present the prevalence, antimicrobial resistance (AMR) mechanisms, and comparative genomics study of 68 Salmonella Kentucky ST198 isolates exhibiting distinct AMR patterns, from patients, food, and environmental sources in Henan Province, China.MethodsWe evaluated the genomic and antimicrobial resistance characteristics of Salmonella Kentucky ST198 obtained from foodborne disease and food safety surveillance in Henan, China, during 2018–2022, using whole-genome sequencing and antibiotic susceptibility testing.Results and discussionAmong 1,574 Salmonella isolates, 68 S. Kentucky ST198 isolates were identified, all of which exhibited multi-drug resistance (MDR). Each strain carried between 5 and 19 antimicrobial resistance genes. Phylogenetic analysis revealed that isolates identified in China were clustered into two clades (ST198-1 and ST198-2), characterized by a specific point mutation in the gyrA gene and closely related to European isolates. Comparative genomics showed that acquisition of MDR region in clade ST198-2 conferred resistance to azithromycin, fosfomycin, cefotaxime, rifamycin, chloramphenicol, florfenicol, trimethoprim, and ampicillin. Most blaCTX-M genes were chromosomally located except one strain carrying blaCTX-M-27 on plasmid p0111. In clade ST198-2, blaCTX-M-55 or blaCTX-M-64 genes were detected within the MDR region, while in clade ST198-1, blaCTX-M-14b was inserted into the coding gene clusters of the T6SS, located chromosomally. Considering the extensively drug-resistant nature of the isolates, continuous surveillance and effective measures to control the transmission of Salmonella Kentucky ST198 are urgently needed.